Antibiotics Susceptibility Pattern of MRSA at Intensive Care Room of Ulin General Hospital Banjarmasin - Shania Indah Chineko; Dewi Indah Noviana Pratiwi; Rahmiati Rahmiati; Noor Muthmainnah; Alfi Yasmina (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2021)
Infection caused by Methicillin-Resistant Staphylococcus aureus (MRSA) is a healthcare-associated infection thatreceives the most significant attention worldwide due to its resistance. Administration of precise and rational antibiotics canprevent high MRSA rates in hospitals. This study aimed to determine the antibiotic susceptibility pattern of MRSA at theintensive care room of Ulin General Hospital, Banjarmasin, between 2016 and 2018. This study was an observational analyticstudy by taking the results of culture and antibiotic susceptibility pattern data of the MRSA isolated from patients treated atthe intensive care room retrospectively. The results showed 37 data of patients suffering from MRSA at the intensive careroom in 2016-2018, with a percentage of 23.81%, 25.81%, and 35.19%, respectively. The most common sources of MRSAisolate in this study were sputum (32.39%), blood (29.27%), and pus (16.67%). From 2016 to 2017, there was a decreasedsusceptibility to macrolide antibiotics, aminoglycosides such as Gentamicin, and quinolones such as Moxifloxacin. In 2018,there was an increased susceptibility pattern of some antibiotics compared to the previous period. Antibiotics with thehighest susceptibility in period of 2016-2018 were Linezolid, Quinupristin/Dalfopristin, Tigecycline, Nitrofurantoin, andTrimethoprim/Sulfamethoxazole. Also, the antibiotic with the lowest susceptibility was Tetracycline. It was concluded thatthere had been changes in some antibiotics' susceptibility pattern to MRSA within 2016-2018.